ANALISIS TEKNIS SISTEM PERALATAN PENGOLAHAN MINYAK KELAPA SKALA KECIL UNTUK KELOMPOK TANI - Silvia Lakumani; Dedie Tooy; Lady E. Ch Lengkey (Universitas Sam Ratulangi, 2022)
ABSTRACT Coconut oil is one of the potential coconut processing products to increase added value for farmers in the North Sulawesi area. The processing of coconut oil has actually been done quite a lot by North Sulawesi farmers, but they still use traditional equipment. This method of processing takes a long time and is inefficient. The government has distributed mechanical equipment for smallscale coconut oil processing and socialized it to several farmer groups. The purpose of this study was to technically analyze the performance of small-scale coconut oil processing systems for 2 farmer groups. This research was conducted with an experimental method in which some of the equipment was tested for its capacity. The material used is coconuts aged 11-12 months, as many as 150 coconuts. Coconut processing on the existing equipment system was carried out in 3 (three) replications, with the number of each replication being 50 coconuts. The stages of coconut processing carried out in this study were, peeling, washing, cleaning, draining, squeezing, separating and allowed to stand for 24 hours. After 24 hours, the resulting coconut cream is put in an oil cooking machine and heated at an average temperature of 1500 C for 2 hours. The results of cooking are filtered, to take the coconut oil. The results showed that the small-scale coconut oil processing equipment system can be maximized to produce commercial coconut oil products. The performance of the tool is influenced by the existing power transmission engine, and the skill of the operator in each stage of work is very important. It is recommended for maximum use of the equipments, given special training to the operators. Keywords: Coconut Oil, Processing Equipment Systems, Farmers, Operators.